Utilization of neem trees (Azadirachta indica) as biopesticide from ancient India to Indonesia: an ethnographic study based on literature review - Muhammad Arif Rahman; Sholeh Hidayat; Ujang Jamaludin; Suroso Mukti Leksono (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
One of the biopesticides is derived from The Neem Tree (Azadirachta indica), which has been widely used in India for centuries. The purposes of this study are to examine the historical use of neem trees as biopesticides in ancient India, the adoption and integration of neem tree-based biopesticides in Indonesian agriculture, the cultural and historical context of neem tree use, and the impact of neem tree-based biopesticides on sustainable agriculture. The research design for this study is an ethnographic approach, which involves the systematic observation, documentation, and analysis of the cultural practices and beliefs related to using neem trees as biopesticides. The findings of this study demonstrate that the Neem tree has been widely described as a biopesticide used to control pests in agriculture in ancient Indian literature, such as the Rigveda and Atharvaveda. The neem tree held cultural and spiritual significance in ancient Indian society, associated with deities and religious beliefs. Historical connections between India and Indonesia facilitated the spread of neem tree-based biopesticides to Indonesia, where they were adopted and integrated into traditional agricultural practices. Indonesian farmers embraced neem tree-based biopesticides and recognized their efficacy in pest control, contributing to sustainable agricultural practices.